2012
DOI: 10.5539/ep.v1n2p21
|View full text |Cite
|
Sign up to set email alerts
|

Natural Ultra Violet Radialtion on Field Grown Rice (Oryza sativa L.) Plants Confer Protection against Oxidative Stress in Seed during Storage under Subtropical Ambience

Abstract: While heat and humidity are known for causing oxidative macromolecular cell damage related seed deterioration during storage under subtropical conditions, information on effect of UV radiation that is also known to cause bio-molecular as well as direct hit damage in plants is largely lacking. A study involving measurements of UV irradiance in seed storage and also over open fields during seed maturation reveals an inverse correlation between genetically conferred (varietally expressed) content of non-enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…As the level of ROS increases, antioxidants degradation exceeds its synthesis and the levels decrease and consequently ROS might continue to accumulate above the critical threshold (Munneé-Bosch. 2005;Shahidi et al, 2006) An increase in MDA during seed storage was reported in many studies (Rao et al 2006;Choudhury and Mandi, 2012) and was indicated to increase gradually with the loss of seed viability. Similarly to the present study, De Oleiveira (2017) found that lipase activity of Moringa seed stored 4°C and 27°C did not change until 12 months of storage but observed a degradation of storage lipids at 18 months of storage.…”
Section: Changes In Polyphenols Flavonoid Frap and Mda Contentmentioning
confidence: 91%
See 3 more Smart Citations
“…As the level of ROS increases, antioxidants degradation exceeds its synthesis and the levels decrease and consequently ROS might continue to accumulate above the critical threshold (Munneé-Bosch. 2005;Shahidi et al, 2006) An increase in MDA during seed storage was reported in many studies (Rao et al 2006;Choudhury and Mandi, 2012) and was indicated to increase gradually with the loss of seed viability. Similarly to the present study, De Oleiveira (2017) found that lipase activity of Moringa seed stored 4°C and 27°C did not change until 12 months of storage but observed a degradation of storage lipids at 18 months of storage.…”
Section: Changes In Polyphenols Flavonoid Frap and Mda Contentmentioning
confidence: 91%
“…Based on fatty acid composition of oil (77% m11onounsaturated, 2% polyunsaturated and 22% saturated) extracted from M. oleifera seed (Lalas and Tsaknis, 2002), it is clear that the seed contains less polyunsaturated fatty acids which are prone to lipid peroxidation. This might be the reason behind the slow increase of MDA in stored Moringa seed compared to other species such as cotton (Goel and Sheoran, 2003) and Oryza sativa L. (Choudhury and Mandi, 2012) where an increase of more than two fold (compared to initial level) was recorded within 24 months or less of storage.…”
Section: Changes In Polyphenols Flavonoid Frap and Mda Contentmentioning
confidence: 98%
See 2 more Smart Citations